The historical and educational subjects in the primary and preschool teachers educational training (Journal of Parents and Teachers, 2014)
In the most common teaching approaches, the history teaching, although it can be never done without "concepts" (dates, names, events ...), is proposed as a questioning look back, knowing that the same questions about the present and its complexity may find relevant answers just having knowledge of the "road trip" we have behind us, and on which we depend, like it or not.
Keywords: Comparative education; history of education; teacher training; curriculum of Education; education; leading names in education